2015
DOI: 10.1007/s00431-015-2561-1
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic superiority of combined propranolol with short steroids course over propranolol monotherapy in infantile hemangioma

Abstract: Combining propranolol with corticosteroids gives a faster response and should be considered in treating life- or function-threatening hemangiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…There were no significant treatment responses when prednisolone was added to propranolol (Table ), unlike the study by Aly et al , which showed that combining propranolol with short steroid courses was superior to propranolol mono‐therapy. This may be explained by the small sample size of our study as well as the study design.…”
Section: Discussionmentioning
confidence: 65%
“…There were no significant treatment responses when prednisolone was added to propranolol (Table ), unlike the study by Aly et al , which showed that combining propranolol with short steroid courses was superior to propranolol mono‐therapy. This may be explained by the small sample size of our study as well as the study design.…”
Section: Discussionmentioning
confidence: 65%
“…Most clinical trials use photography and measure surface area of the IH because MRI has cost and convenience issues even though it is most useful for IH evaluation. 18,[22][23][24][25][35][36][37] Moreover, the radiologist evaluated the volume independently and blindly. Third, this study had a very low dropout rate compared with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…72 In a randomized controlled trial (RCT) of oral propranolol compared with observation for IHs, the overall efficacy of propranolol (defined as excellent, good, or medium response) was 98.97%, compared with 31.25% in the observation group (P < .05). 73 Last, Aly et al 74 compared oral propranolol alone versus oral propranolol combined with 2 weeks of "priming" with oral prednisolone. Those in the prednisolone-primed propranolol group showed a statistically superior reduction in IH size at weeks 2, 4, and 8 compared with the propranolol group, but the 6-month response was equivocal for both groups regarding all assessed variables.…”
Section: Management: Pharmacotherapymentioning
confidence: 99%